Pain in patients attending a specialist cancer service: prevalence and association with emotional distress. - O'Connor, M; Weir, J; Butcher, I; Kleiboer, A; Murray, G; Sharma, N; Thekkumpurath, P; Walker, J; Fallon, M; Storey, D; Sharpe, M (2012)
CONTEXT: We know little about how many outpatients of a modern cancer center suffer from clinically significant unrelieved pain and the characteristics of these patients to guide better care. OBJECTIVES: To determine the prevalence of clinically significant pain (CSP) in the outpatients of a regional cancer center and the association with distress and other variables. METHODS: A secondary analysis of cross-sectional, self-reported and clinical data from 2768 patients reattending selected clinics of a regional National Health Service cancer center in the U.K. Pain was measured using the pain severity scale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire, emotional distress was measured by the Hospital Anxiety and Depression Scale, and demographic and clinical data were taken from medical records. RESULTS: Fifty-four percent (95% confidence interval [CI] 52-56) of patients reported pain at least "a little" in the previous week and 18% (95% CI 17-20) at least "quite a bit" (CSP). The strongest independent associations of CSP were active disease (odds ratio [OR] 1.95, 95% CI 1.5-2.5) and emotional distress (OR 4.8, 95% CI 4-6). CONCLUSION: CSP is surprisingly common in outpatients of specialist cancer services, and it is strongly and independently associated with emotional distress. Better symptom management should consider pain and distress together.